MEREDUKSI AGRESIFITAS DENGAN COGNITIVE BEHAVIORAL ART TERAPY PADA SISWA SMPN 14 PONTIANAK - Putri, Amallia; Yuline, Yuline (Academy of Education Journal, 2023)
The aim of this study was to test the effectiveness of group counseling with cognitive behavioral art therapy in reducing aggression using a mixed methods model embedded in an experiment. The scale used is the Buss and Pery aggressiveness scale (Garofalo, 2018) with a total of 30 statement items. Based on data analysis, the average pretest value was 83.7 and after being given CBAT treatment the posttest value was 57.8 with a Wilcoxon sign-rank test Z value of -2.201, with a p value of 0.028, which means the p value is smaller than 0.05. So it can be concluded that Ha is accepted and Ho is rejected, which means that cognitive behavioral art therapy group counseling is effective in reducing student aggression. Viewed qualitatively analysis of counseling conversations with high aggressiveness Referring to harsh words, being angry, negotiating, does not reduce emotional control. The changes that occur are in the moderate to low category, this shows that cognitive behavioral art therapy group counseling has a therapeutic impact on group members who are counselees.